IgG4 immune response in Churg–Strauss syndrome. Issue 3 (25th November 2011) - Vaglio, Augusto; Strehl, Johanna D; Manger, Bernhard; Maritati, Federica; Alberici, Federico; Beyer, Christian; Rech, Jürgen; Sinico, Renato A; Bonatti, Francesco; Battistelli, Luisita; Distler, Jörg H W; Schett, Georg; et al.
Abstract : Objective: T-helper type 2 responses are crucial in Churg–Strauss syndrome (CSS) and may enhance the production of IgG4 antibodies. The authors assessed the IgG4 immune response in CSS patients. Methods: The authors included 46 consecutive patients with CSS (24 with active and 22 with quiescent disease), 26 with granulomatosis with polyangiitis (GPA, Wegener's), 25 with atopic asthma and 20 healthy controls and determined serum IgG, IgM, IgA, IgE and IgG subclass levels. Tissue infiltration by IgG4 plasma cells was assessed in nine patients with CSS, 10 with GPA, 22 with chronic sinusitis (11 with and 11 without eosinophilia). Results: IgG4 levels were markedly higher in active CSS patients than in controls (p<0.001 vs all control groups). Serum IgG4 correlated with the number of disease manifestations (r=0.52, p=0.01) and the Birmingham vasculitis activity score (r=0.64, p=0.001). Longitudinal analysis in 12 CSS cases showed that both the IgG4 level and IgG4/IgG ratio dropped during disease remission (p=3×10 −5 and p=6×10 −4, respectively). Tissue analysis did not show an increased IgG4 plasma cell infiltration in CSS biopsies compared with control groups. Conclusions: Serum IgG4 levels are markedly elevated in active CSS and correlate with the number of organ manifestations and disease activity.